Analysis of Factor Factors That Influence The Implementation of Financial Management Information System (SIMDA) Financial Study - Febrina Sinta Fitriani; Endang Masitoh (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
The purpose of this study is to empirically examine the influence of the expertise of system users, education and training programs, information technology and top management support for SIMDA Finance in Village Office in Sub-District Jebres Surakarta. The population in this study is the District of Jebres District with a sample using purposive sampling obtained a sample of 30 respondents. The results showed that the variables of system user expertise, education and training programs as well as top management support had a significant effect on SIMDA Finance, while the information technology variable had no effect on SIMDA Finance.